Event management knowledge domains as the antecedents for successful cultural events in Malaysia / Qistina Donna Lee Abdullah - Lee Abdullah, Qistina Donna (Institute of Graduate Studies, UiTM, 2014)
Event management is currently becoming a blooming industry in the world. It has been recognized as a new dimension in business network for funds exchange and capital income apart from generating vast career opportunity in the market. The revenue collected from events are various according to its category such as events in the tourism industry, destination attractions, cultural and festivals, MICE industry, national and international events. In Malaysia, cultural events and festival have be converted into a prospect developing area for government, agencies and private sectors to engage. Apart from formulate earnings, this sector also help to secure and preserve the authenticity of Malaysian arts, cultural and heritage. Acknowledge the significant of event management existence, therefore this study is establish to investigate the practice of event management knowledge domains as the antecedents for successful cultural events in Malaysia.